SYSTEM OF INVESTMENT POLICY INSTRUMENTS AT THE LOCAL LEVEL: THEORETICAL ASPECT - Malyshivskyi , T.V.; Stefinin, V.V. (The actual problems of regional economy development, 2021)
The aim of the article is to form a theoretical basis for the development of a unified system of investment policy instruments at the local level for its further use by local governments and local authorities in the process of developing and implementing local investment policy. In the course of the research the methods of analysis, systematization, grouping, abstraction were used in order to determine the normative documents on regulating the activities of investments attraction by local governments, isolate and consider investment policy instruments at the local level. The information base of the scientific research consisted of scientific works of domestic and foreign economists and legislative and regulatory documents on regulating the activities of local governments. The theoretical foundations of the system of investment policy instruments at the local level have been studied. This is due to the fact that local governments differ significantly in their responsibilities and powers from both central and local authorities, and therefore need their own system of tools to create local investment attractiveness. Based on the system of investment instruments that is used or can be used at the national level, as well as taking into account the Law of Ukraine "On Local Self-Government in Ukraine" we have proposed an author's system of investment policy instruments that can be used at the local level. This system of instruments consists of instruments of direct influence (financial instruments) and indirect ones, which in turn determine the level of institutional capacity of the community to attract investment. Instruments of direct influence include tax instruments, formation of trust funds, joint financing of investment activities, holding competitions to provide funding for winners, creation of special free economic zones, etc. The tools of indirect influence include: establishing a system of communication with investors; formation and dissemination of community investment proposals; development and distribution of promotional materials for the investor (investment passport, guide for the investor, etc.) and others. The scientific novelty of the obtained results is the creation of an author's system of investment policy instruments at the local level. The results of the study can be used by local authorities in developing and implementing community investment policy. We believe that the use of these tools can increase the level of both the institutional capacity of the community to attract investment and the level of investment attractiveness of the community as a whole.